Two Series of Homodinuclear Lanthanide Complexes: Greatly Enhancing Energy Barriers through Tuning Terminal Solvent Ligands in Dy2 Single‐Molecule Magnets. Issue 21 (9th October 2017) - Qin, Yaru; Zhang, Haifeng; Sun, Hao; Pan, Yangdan; Ge, Yu; Li, Yahong; Zhang, Yi‐Quan
Abstract: The utilization of 2‐ethoxy‐6‐{[(2‐hydroxy‐3‐methoxybenzyl)imino]methyl}phenol (H2 L) as a chelating ligand, in combination with the employment of alcohols (EtOH and MeOH) as auxiliary ligands, in 4 f‐metal chemistry afforded two series of dinuclear lanthanide complexes of compositions [Ln2 L2 (NO3 )2 (EtOH)2 ] (Ln=Sm (1 ), Eu (2 ), Gd (3 ), Tb (4 ), Dy (5 ), Ho (6 ), Er (7 )) and [Ln2 L2 (NO3 )2 (MeOH)2 ] (Ln=Sm (8 ), Eu (9 ), Gd (10 ), Tb (11 ), Dy (12 ), Ho (13 ), Er (14 )). The structures of1 –14 were determined by single‐crystal X‐ray crystallography. Complexes1 –7 are isomorphous. The two lanthanide(III) ions in1 –7 are doubly bridged by two deprotonated aminophenoxide oxygen atoms of two μ2 :η 0 :η 1 :η 2 :η 1 :η 1 :η 0 ‐L 2− ligands. One nitrogen atom, two oxygen atoms of the NO3 − anion, two methoxide oxygen atoms of two ligand sets, and one oxygen atom of the terminally coordinated EtOH molecule complete the distorted dodecahedron geometry of each lanthanide(III) ion. Compounds8 –14 are isomorphous and their structures are similar to those of1 –7 . The slight difference between1 –7 and8 –14 stems from purposefully replacing the EtOH ligands in1 –7 with MeOH in8 –14 . Direct‐current magnetic susceptibility studies in the 2–300 K range reveal weak antiferromagnetic interactions for3, 4, 7, 10, 11, and14, and ferromagnetic interactions at low temperature for5, 6, 12, and13 . Complexes5 and12 exhibit single‐molecule magnet (SMM) behavior with energy barriers of 131.3 K for5 and 198.8 K for12 . The energy barrier is significantly enhanced by dexterously regulating the terminal ligands. To rationalize the observed difference in the magnetic behavior, complete‐active‐space self‐consistent field (CASSCF) calculations were performed on two Dy2 complexes. Subtle variation in the angle between the magnetic axes and the vector connecting two dysprosium(III) ions results in a weaker influence on the tunneling gap of individual dysprosium(III) ions by the dipolar field in12 . This work proposes an efficient strategy for synthesizing Dy2 SMMs with high energy barriers. Abstract : Small‐scale attraction : Two series of binuclear lanthanide complexes, [Ln2 L2 (NO3 )2 (EtOH)2 ] and [Ln2 L2 (NO3 )2 (MeOH)2 ], were prepared. Of these complexes, two compounds of dysprosium exhibit single‐molecule magnet behavior. The energy barrier is enhanced by about 67 K through changing the terminal solvent ligands from EtOH to MeOH.